The relationship between communication and job satisfaction among older and younger academic staff at UiTM Pahang / Nurul Hidayah Mohd Khalid - Mohd Khalid, Nurul Hidayah (2015)
The title for this research is "The relationship between communication and job satisfaction among older and younger academic staff at Universiti Teknologi Mara (UiTM) Jengka Pahang". The purposes of this study are to find out the problems of miscommunication between older and younger academic staff at UiTM Jengka Pahang, to identify how they communicate and to find out the level of satisfaction working between them. The population of respondents for this study is only 55 academic staff at UiTM Jengka Pahang that was randomly selected. A questionnaire has been used as a medium to distribute to them. These researches want to identify whether academic staff at UiTM Jengka Pahang has a good communication or not in order to ensure they have a higher level of satisfaction working. Based on the findings it shows that the majority of the respondents are female, their age are less than («) 40 years old, level of employment are 1 to 5 years and came from Faculty of Business Management. The data was analyzed by using the Statistical Package in the Social Science (SPSS) software version 21 and involves the correlation test. The finding shows that there has a good relationship between communication and job satisfaction among older and younger academic staff at UiTM Jengka Pahang.